2003
DOI: 10.1007/s00431-003-1209-8
|View full text |Cite
|
Sign up to set email alerts
|

Urinary lithogenic and inhibitory factors in preterm neonates receiving either total parenteral nutrition or milk formula

Abstract: In preterm neonates on total parenteral nutrition, urinary oxalate -to-creatinine ratio (a potent lithogenic factor) was lower and urinary citrate -to-creatinine ratio (a lithoprotective factor) also lower than in formula fed neonates. The type of feeding (total parenteral nutrition or special preterm milk formula) seems to affect urinary oxalate and citrate but not calcium and magnesium in non-furosemide treated preterm infants during the first 3 weeks of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Hypercalciuria, e.g., induced by furosemide (and dexamethasone) treatment, plays a major role in the pathophysiology of nephrocalcinosis [9,14]. Furthermore, in the last decade, several urinary lithogenic (oxalate) and inhibitory (citrate, magnesium) substances have been studied as possible modifying factors during the development of renal calcification [15,16,17,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Hypercalciuria, e.g., induced by furosemide (and dexamethasone) treatment, plays a major role in the pathophysiology of nephrocalcinosis [9,14]. Furthermore, in the last decade, several urinary lithogenic (oxalate) and inhibitory (citrate, magnesium) substances have been studied as possible modifying factors during the development of renal calcification [15,16,17,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that breast-fed premature infants have lower Ox/Cr ratios than formula-fed neonates during the first 2 months of life. Giapros and colleagues found a lower urinary Ox/Cr ratio in preterm neonates on total parenteral nutrition than in formula-fed neonates (Giapros et al 2003). Contrary to these results, Hoppe and colleagues found higher oxalic acid excretion in preterm infants under parenteral nutrition (Hoppe et al 1993).…”
Section: Discussionmentioning
confidence: 92%
“…Higher urinary oxalate excretion was observed in formula-fed than in breastfed infants (Campfield et al 1994;Hoppe et al 1997;Morgenstern et al 1993). Parenteral feeding also seems to affect urinary oxalate excretion in preterm and term infants (Giapros et al 2003;Hoppe et al 1993).…”
Section: Introductionmentioning
confidence: 92%
“…Minimal (trophic) enteral nutrition is initiated within the first 48 h of birth. The feeding principle and the amounts of calories, proteins and minerals given by enteral or parenteral nutrition have been reported elsewhere [12]. Detailed information about nutrition was collected at each time point, including information on the quantity and type of formula milk, the duration of breast feeding and whether partial or exclusive and the age at which solid foods were introduced as well as their type and quantities were collected by means of a food questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…calcium (Ca) and oxalate (Ox)] and stoneinhibiting [e.g. citrate (Cit) and magnesium (Mg)] factors [6][7][8][9][10][11][12]. In the majority of patients, spontaneous resolution of NC occurs in the first years of life, but persistence for several years has been described [13][14][15].…”
Section: Introductionmentioning
confidence: 99%